Spectroscopy of low lying states in 136Cs. (February 2016) - Rebeiro, B; Triambak, S; Lindsay, R; Adsley, P; Burbadge, C; Ball, G; Bildstein, V; Faestermann, T; Garrett, PE; Hertenberger, R; Radich, A; Rand, E; et al.
Abstract: The low-lying excited states in 136 Cs relevant to the double beta decay of 136 Xe were studied via a 138 Ba(d, α) 136 Cs transfer reaction with a high resolution magnetic spectrometer. Preliminary results from the experiment are presented.